Evaluation of intranasal canine parvovirus vaccination in dogs - Murugesan V (Department of Veterinary Epidemiology and Preventive Medicine,College of Veterinary and Animal Sciences, 2010)
Present study was carried out to evaluate the potency of intranasal canine parvovirus vaccination in dogs at the Department of Veterinary Epidemiology and Preventive Medicine, College of Veterinary and Animal Sciences, Mannuthy during the period 2009-2010. The post vaccination immune response of intranasal CPV vaccination and the interference of MDA were assessed by HI and SN tests. The vaccine performance was studied in twelve unvaccinated healthy pups of six to eight weeks age. The blood samples were collected before vaccination for assessment of the CPV antibodies by HI test and the pups were grouped into two viz., Group 1 (G1) having HI titre of ≤80 (range, 0 to 80) and Group 2 (G2) having HI titre of >80 (range, 160 to 320). Intranasal vaccination has been done based on two different schedules viz., Schedule I and II. Schedule I was performed by using one drop of attenuated CPV-2 antigen each dose containing 103 TCID50 antigenic mass through intranasal route on day zero and day two. Schedule II was performed using the same antigen intranasally on day zero, day two and day four. Seroconversion was considered when pups developed a fourfold or greater increase in HI titre to a level ≥ 80. Hundred percent of the pups were seroconverted in both groups and had protective titre against CPV disease. In group I animals, the range of geometric mean HI titre from day zero to day 90 post vaccination was 30.58 to 2560. The titre also increased from day seven to day 90 and the differences between consecutive sampling intervals were statistically significant (P<0.05). In group II animals, the range of geometric mean HI titre recorded from zero to 90th day post vaccination were 201.58 to 1436.75. Active immune responses after vaccination were observed in all pups but a fall in immune response was noticed on 7th day with a geometric mean HI titre of 126.99 compared to the geometric mean HI titre of 201.58 on day zero. Statistically significant difference in titre was observed only on 90th day. The pattern of seroconversion in SN titres on day zero to day 90 post inoculation was similar to that of HI test in both groups. All the pups belonging to group I had seroconversion within a week or two after vaccination. All pups belonging to group II had a good titre of seroconversion on day 90, and surpassed the maternal antibody interference with a geometric mean HI titre as high as 201.58. In both groups, slight fall in seroconversion titre was noticed on 60th day post vaccination in all pups which may be due to some stress or immunogenic unresponsiveness. None of the vaccinated pups developed anaphylaxis or other adverse reactions attributable to the vaccine and no viral shedding in the faeces following vaccination. All the pups in both tested groups survived in good health during the post vaccination monitoring period of one year and none of the pups showed any clinical signs of CPV disease. The vaccine was well tolerated by the dogs and there were no adverse effects. The findings of this study suggested that good protection against CPV infection may be achieved by the use of attenuated CPV-2 antigen with a titre of 103TCID50 per dose administered intranasally based on both schedules. This minimal vaccine mass was able to induce active immune responses in all pups with MDA titres of ≤ 80 with a range of zero to 80 according to schedule I and > 80 with a range of 160 to 320 according to schedule II by intranasal route and may confer more adequate protection than that of oral and parentral routes. This method of immunization was proved simple, convenient, reliable, safe, painless and efficacious. Hence, both vaccination schedules could be recommended for immunoprophylaxis under field conditions against CPV disease in dogs.